(3bdGFO fMhQ GdMhQ aj Yde GdYQhVs - (3CHh eMeO YHO Gddg Hf eMeO GdCfUGQj GdCfOdSj, GHf CHj GdLjT GdeZQHj,J (B627 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Ydi Cf bUQ SdGeI GdWHY Ydi fhY GdEfSGf hCVeQ aj Wj UOhQge VQhH GdChRGf s
(3BNQgG (B:s
(3hgPG YfO GdCNaT hGeG YfO GdNdjd adgG HMQ hGMO hgPG eG CQOfG ef HjGf eTcdGJ GdeNJUQ aj Yde GdYQhV s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3SYjO GdOjhg Lj (B(123) s
Keywords: (3GdYQhV hGdbhGais